More scalable solution for multi-robot-multi-target assignment problem - Marangoz, Salih; Amasyali, Mehmet Fatih; Uslu, Erkan; Cakmak, Furkan; Altuntas, Nihal; Yavuz, Sirma (ELSEVIER, 2019)
During multi-robot exploration, the calculation cost of the target assignment increases significantly with an increase in the map size and number of robots. In this study, a target elimination method is proposed to overcome this challenge. The benefit of the proposed method increases as the map size and number of robots increase, which is demonstrated both empirically and theoretically. Moreover, it is established that the proposed method does not rely on a specific map representation or robot-target assignment method. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Exploration; Multi-robot; Multi-target; Assignment; Target elimination; Automation & Control Systems; Computer Science; Robotics